Direito internacional dos refugiados: as dificuldades no tratamento dos refugiados no Brasil - Belardinucci, Luiza (My University, 2022)
International Refugee Law is the field of Legal Sciences dedicated to the protection of these individuals. Given to this, the study proposes to analyse the sufficiency and effectiveness of the current public policies related to the flow of displaced people in the country. The number of refugees in Brazil rises each day, especially because of the migration crisis in Latin America and in the world, and the Covid-19 pandemic, thus determining the relevance of the study. The research analysed data and indexes related to the refugees in the country, especially under the International Refugee Law; in addition to analysing national and international legislation, obstacles of every nature perceived by these peoples and presented suggestions for the remedying these obstacles. For that, and through the dialectical-deductive method, information was gathered on the legislation related to these subjects, on the mechanisms currently implemented in the country, also identifying divergent points between theory and normative application. In this light, the study reached important results, pointing to the need for greater effort by the various state and civil actors, in addition to bringing the refugee to the centre of the debate; however, it also identified the enormous governmental effort in dealing with the matter. The document fulfils its objective, in addition to organizing the information available on the subject, serving as a basis for future studies, especially from the perspective of identifying divergences and pointing out solutions. [resumo fornecido pelo autor]
O Direito Internacional dos Refugiados é o campo das Ciências Jurídicas destinado à proteção desses indivíduos. Diante disso, o presente estudo propõe-se a analisar a suficiência e efetividade das políticas públicas brasileiras atuais em relação ao fluxo de povos deslocados no país. O número de refugiados no Brasil aumenta a cada dia, especialmente em razão das crises migratórias na América Latina e no mundo, e da pandemia de Covid-19, determinando, assim, a relevância do estudo. A pesquisa analisou dados e índices relacionados aos refugiados no país, especialmente sob a ótica do Direito Internacional dos Refugiados, além da analisar a legislação pátria e internacional, os obstáculos de toda natureza percebido por esses povos e apresentou sugestões para o saneamento desses obstáculos. Para tanto, e através do método dialético-dedutivo, foram levantadas informações sobre a legislação atinente a esses sujeitos, sobre os mecanismos implementados no país atualmente, além de identificar pontos divergentes entre a teoria e a aplicação normativa. Sob esse prisma, o estudo chegou à importantes resultados, apontando a necessidade de maior envidamento de esforços pelos diversos atores estatais e civis, além de trazer o refugiado para o centro do debate, entretanto, também identificou o enorme esforço governamental na tratativa da matéria. O documento cumpre o seu objetivo, além de organizar as informações disponíveis sobre a temática, servindo de base para estudos futuros sobre o tema, especialmente sob a ótica da identificação de divergências e apontamentos de soluções. [resumo fornecido pelo autor]
Keywords: Direito; Refugiados; Direito de asilo; Direito internacional privado; Direito internacional público e direitos humanos